PROVIDING OF ACCURACYOF THE DEFORMATION CHARACTERISTICS MEASUREMENT - A. S. Romankov (Литьë и металлургия)
In the article there is shown that at measuring of deformation characteristics using strain gage the high accuracy is provided, which complies with requirements of testing standards.